Health‐related quality of life and long‐term outcomes after endoscopic therapy for walled‐off pancreatic necrosis. Issue 1 (30th September 2018) - Smith, Zachary L.; Gregory, Martin H.; Elsner, Jeffrey; Alajlan, Bader A.; Kodali, Divya; Hollander, Thomas; Sayuk, Gregory S.; Lang, Gabriel D.; Das, Koushik K.; Mullady, Daniel K.; Early, Dayna S.; Kushnir, Vladimir M.
Abstract : Background and Aim: Walled‐off pancreatic necrosis (WON) frequently develops after necrotizing pancreatitis. Endoscopic drainage has become the preferred modality for symptomatic or infected WON. The aim of the present study was to assess health‐related quality of life (HR‐QOL) and long‐term outcomes in patients undergoing endoscopic drainage for WON. Methods: Patients undergoing endoscopic drainage of WON from January 2006 to May 2016 were identified. Data recorded included demographic information, and the incidence of long‐term sequelae including pancreatic endocrine and exocrine insufficiency. Attempts were made to contact all patients. HR‐QOL was assessed using the SF‐36 questionnaire. Results: Eighty patients were analyzed, 41 (51.3%) of whom completed the SF‐36. One‐year all‐cause mortality was 6.2%, and disease‐related mortality was 3.7%. A notable proportion of patients developed exocrine insufficiency (32.5%), endocrine insufficiency (27.7%), and long‐term opiate use (42.5%). Development of exocrine insufficiency was predictive of lower total SF‐36 scores ( P = 0.016). Patients with WON had better HR‐QOL compared with cohorts of irritable bowel syndrome (IBS) and inflammatory bowel disease (IBD). In patients developing exocrine insufficiency versus healthy controls, poorer scores in the physical role ( P < 0.001), general health ( P < 0.001), vitality ( P = 0.001), and emotional role ( P = 0.029) domains were observed. Exocrine insufficiency patients had better HR‐QOL than the IBS and IBD cohorts, although these differences were less pronounced. Conclusion: After undergoing endoscopic drainage for WON, patients have relatively preserved HR‐QOL. The subset of patients that develop exocrine insufficiency have significantly poorer HR‐QOL compared to healthy controls, although not to the degree of chronic gastrointestinal disorders such as IBS and IBD.